2011
DOI: 10.1016/j.brainres.2011.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Pristanic acid promotes oxidative stress in brain cortex of young rats: A possible pathophysiological mechanism for brain damage in peroxisomal disorders

Abstract: Pristanic acid (Prist) is accumulated in various peroxisomal disorders characterized by severe neurological dysfunction whose pathogenesis is poorly understood. Since oxidative damage has been demonstrated in brain of patients affected by neurodegenerative disorders, in the present work we investigated the in vitro effects of Prist on important parameters of oxidative stress in cerebral cortex from young rats. Prist significantly increased malondialdehyde levels, reflecting an increase of lipid peroxidation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…Sulfhydryl groups of proteins are oxidized by reactive free radicals giving rise to carbonyl levels. It is therefore presumed that attack of reactive species which are induced by this short branched chain fatty acid leads to the oxidative damage to proteins (Leipnitz et al, 2011). Our results corroborate this observation as PC content increased dose dependently on being exposed to VPA in cerebral cortex and cerebellum.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Sulfhydryl groups of proteins are oxidized by reactive free radicals giving rise to carbonyl levels. It is therefore presumed that attack of reactive species which are induced by this short branched chain fatty acid leads to the oxidative damage to proteins (Leipnitz et al, 2011). Our results corroborate this observation as PC content increased dose dependently on being exposed to VPA in cerebral cortex and cerebellum.…”
Section: Discussionsupporting
confidence: 87%
“…ROS have been associated with many pathophysiological conditions such as cancer and in various neurodegenerative diseases (Leipnitz et al, 2011). Under normal physiological conditions, a delicate balance exists between the rate of ROS formation and the rate of their neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these observations, we have recently shown that Prist markedly induces oxidative damage, reduces the antioxidant defenses (Leipnitz et al,2011), and compromises neurotransmission and the electron flow through the respiratory chain in brains of young rats (Busanello et al,2011). However, to our knowledge, nothing has been reported on the effects of Prist on other important parameters of mitochondrial energy homeostasis, such as the respiratory parameters states 3 and 4, respiratory control ratiom and ADP/O ratio determined by oxymetry, as well as on mitochondrial NAD(P)H levels, membrane potential, and swelling.…”
supporting
confidence: 54%
“…We always carried out parallel experiments with various blanks (controls) in the presence or absence of Prist (20–100 μM) or Palm (100 μM) and also with or without mitochondrial preparations in the reaction medium to detect any interference (artifacts) of these fatty acids on the techniques utilized to measure the mitochondrial parameters. The tested Prist doses were based on the concentrations of this fatty acid found in plasma of patients affected by some peroxisomal disorders and in previous reports showing cytotoxic effects of Prist on neural cells (Ferdinandusse et al,2000; McLean et al,2002; Kahlert et al,2005; Thompson et al,2008; Rönicke et al,2009; Smith et al,2010; Leipnitz et al,2011; Busanello et al,2011).…”
Section: Methodsmentioning
confidence: 99%
“…Note that pristanic acid apparently exerts its toxic effect mainly through its protonophoric action, at least in human skin fibroblasts (Komen et al, 2007). When given to post-nuclear supernatant fractions prepared from rat brain cortex, pristanic acid also causes ROS-generation, as evidenced by decreased GSH levels and increased levels of MDA and protein oxidation (Leipnitz et al, 2011;Busanello et al, 2014). In mitochondrial preparations of rat brain, pristanic acid decreases the m and NAD(P)H levels and causes mitochondrial swelling.…”
Section: Pristanic Acidmentioning
confidence: 99%